CSR Program PT. Pertamina Hulu Mahakam Towards the Empowerment of Farmer Women Groups in Muara Sembilang Village, Kutai Kartanegara Regency - Wahid, Jumiati; Malik, Dhea Ananda; B, Jauchar; Nurmiyati, Niken (HK-Publishing, 2024)
AbstractThe purpose of this research is to describe the Implementation of PT's CSR Program. Pertamina Hulu Mahakam towards the Empowerment of Women Farmer Groups in Muara Sembilang Village, Kutai Kartanegara Regency. This research uses qualitative research techniques, which is a research method to obtain descriptive data results in the form of describing observation results through words and verbally from objects and subjects. The research results show that PT Pertamina Hulu Mahakam cares in providing assistance and assistance to the Women's Farmer Group (KWT) in Muara Sembilang Village. Empowerment is carried out as a proof of social responsibility carried out by PHM to create citizens who are empowered and utilize family medicinal plants (toga) for their daily living needs. Apart from that, PHM is also committed to providing assistance and monitoring of the program, at least once every 3 months PHM always comes to supervise by collaborating with LPM.Keywords: CSR, Pertamina Hulu Mahakam, Women Farmers GroupÂ